2017
DOI: 10.1097/sla.0000000000002147
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Liver Resection for Colorectal Metastases in Elderly and Octogenarian Patients

Abstract: In patients over 70 years of age laparoscopic liver resection, for colorectal liver metastases, offers significant lower morbidity, and a shorter hospital stay with comparable oncological outcomes when compared with open liver resection. However, the benefits of the laparoscopic approach appear to fade with increasing age, with no statistically significant benefits in octogenarians except for a lower High Dependency Unit stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
99
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 48 publications
7
99
1
1
Order By: Relevance
“…Literature review revealed three other studies performed on liver resection in octogenarians, plus one study with a subset of octogenarians . Martínez‐Cecilia et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature review revealed three other studies performed on liver resection in octogenarians, plus one study with a subset of octogenarians . Martínez‐Cecilia et al .…”
Section: Discussionmentioning
confidence: 99%
“…Short‐term and perioperative outcomes from liver resection in octogenarians have been determined previously . Riffat et al .…”
Section: Introductionmentioning
confidence: 99%
“…The mortality in these cases was not really due to age, but rather comorbidities and PLA complications in patients with comorbidities; these factors were more important than age alone. Recently, Martínez-Cecilia et al reported that octogenarians have comparable outcomes to younger people in colorectal liver metastases when treated with laparoscopic liver resection [36]. Thus, comorbidity and complications are more important prognostic factors than age.…”
Section: Discussionmentioning
confidence: 99%
“…Laparotomy has long been the preferred surgical approach but laparoscopic liver resection (LLR) is gaining popularity. Advantages of LLR include a quicker recovery and reduced morbidity leading to the consensus that laparoscopy should be considered the standard approach to minor liver resections. However, repeat liver resection is considered a challenging procedure owing to adhesions, anatomical distortion caused by the previous liver resection and other treatment modalities that are often used in the setting of recurrent disease.…”
Section: Introductionmentioning
confidence: 99%